PENELUSURAN MISKONSEPSI MAHASISWA TENTANG MATRIKS MENGGUNAKAN CERTAINTY OF RESPONSE INDEX - Suastika Suastika; Theo Jhoni H.; Titik Utami (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Physics is closely related to mathematics. Mathematics is the language of science physics. Matrices was one of study material taught in Physics Education Study Program in University of Palangka Raya. This research was aimed to explore student misconceptions about the concepts of matrices. This research was carried out after the implementation of learning activities subject Matrices and Vector Spaces to 40 students for academic year 2014/2015. The student misconceptions was identified with Certainty of Response Index (CRI).  It was found that 78.75% of the students understand concepts and 21.25% of the students does not understand the concept. Lack of understanding of students associated with matrices algebra and the completion of linear equations by reducing the matrix to row echelon form. The use of CRI can distinguish between students who have misconceptions with students who lack of knowledge.Keywords: misconception, science, matrices, CRI.